The relationship between student satisfaction and online learning interaction at a South African Institution of Higher Learning (IHL) - Zindove, Problem (Rhodes University, Faculty of Commerce, Department of Management)
Institutions of Higher Learning (IHLs) are key providers of skilled labour that drive economic growth. Therefore, it is crucial to ensure that students are satisfied with their interaction in the learning environment, including interaction with peers, instructors, and course content. This satisfaction is vital for positive learning outcomes. The COVID-19 pandemic prompted a shift from traditional face-to-face to online learning, significantly affecting student interaction. This research aimed to explore the relationship between online learning interaction and student satisfaction at a selected South African IHL. A comprehensive review of the South African higher education landscape, online learning interaction, and student satisfaction literature was conducted. Based on this review, a hypothesised model was proposed, identifying the independent variable (and its constructs namely, learner-to-learner interaction, learner-to-instructor interaction, and learner-to-content interaction) that may influence the dependent variable- student satisfaction (encompassing both expectations and experience). The research employed a positivistic approach using a deductive reasoning and quantitative methodology. A survey strategy, consisting of self-administered online and paper-based questionnaires, was used to gather data from a convenience sample of students registered at an IHL in South Africa. A total of 268 usable responses were analysed statistically. The validity and reliability of the measurement instrument were confirmed. Descriptive and inferential statistics, including standard deviation, Pearson`s correlation coefficients, regression analysis, and Analysis of Variance (ANOVA) were applied in the data analysis. The results revealed a statistically significant relationship between online learning interaction (independent variable) and student satisfaction (dependent variable), leading to the acceptance of the hypotheses. No modifications were necessary, as the hypothesised model provided a good fit. This research contributes to the body of knowledge on student satisfaction in online learning interaction within South African IHLs. Its use of the Community of Inquiry (CoI) framework has provided a comprehensive perspective of the online learning interaction variable. Also, this research is among the few that juxtaposed student expectations and student experience in student satisfaction discourse. Furthermore, it was found that the constructs of learner-to-learner interaction and learner-to-instructor interaction have an equally strong and statistically significant relationship with student satisfaction, compared to the learner-to-content interaction construct. It also offers practical, methodological recommendations for IHLs to adopt and implement online learning courses effectively. Among others, the adoption of online learning at IHLs should be encouraged as it leads to student satisfaction. Tangent to this is the need for instructor training programmes on online pedagogy. Future research should also consider qualitative research design to get rich insight into Why and How the relationship between online learning interaction and student satisfaction exists.
Keywords: Education, Higher -- South Africa; Web-based instruction -- South Africa; E-learning; Interaction analysis in education; Student satisfaction